Becoming a Mathematician - Wood, Leigh N. author. aut Link
VIII, 188 p.
Keywords: Mathematicians are everywhere and nowhere: although they play key roles in industry and research, business and science, the people who use the ideas and tools of the mathematics are often invisible and difficult to identify. This leads to a lack of clarity for students who are studying the mathematical sciences in their transition to professional life. Becoming a Mathematician considers the process of developing a mathematical identity and becoming a mathematician from the point of view of the participants in the process – students and recent graduates. It focuses on the people who do mathematics rather than on the topics of mathematics. It investigates the development of mathematical scientists for a variety of workplaces, and incorporates the experiences of those who were unsuccessful as well as those who were successful in the transition to the profession. The research presented is based on interviews, observations and surveys of students and graduates as they develop their identity as mathematicians, carried out over a decade in Australia and a diverse range of countries.